Analisis Minat Beli Pada Merek Produk Kecantikan A Melalui Shopee Live - Octoviana, Angel; Wolor , Christian Wiradendi; Utari , Eka Dewi (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This study aims to find out more deeply about the buying interest held by shopee e-commerce users who choose a digital shopping method using the Shopee Live feature. The background of this research is based on the phenomenon of people choosing to use digital technology to fulfill one of their life needs. The research method used in this research is a qualitative method with descriptive analysis and collecting data by interview, observation, and documentation. The results of this study indicate that the quality of Shopee Live from beauty brand A has a good level of quality, with the results of the analysis that the existing broadcasters are able to provide informative product explanations. Discounts are a way to increase consumer buying interest. In addition to discounts, reviews of consumer satisfaction also play a role in building buyer confidence to use the product. Consumers who are satisfied will form consumer loyalty.